-10-6x=14-9x

Simple and best practice solution for -10-6x=14-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10-6x=14-9x equation:


Simplifying
-10 + -6x = 14 + -9x

Solving
-10 + -6x = 14 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-10 + -6x + 9x = 14 + -9x + 9x

Combine like terms: -6x + 9x = 3x
-10 + 3x = 14 + -9x + 9x

Combine like terms: -9x + 9x = 0
-10 + 3x = 14 + 0
-10 + 3x = 14

Add '10' to each side of the equation.
-10 + 10 + 3x = 14 + 10

Combine like terms: -10 + 10 = 0
0 + 3x = 14 + 10
3x = 14 + 10

Combine like terms: 14 + 10 = 24
3x = 24

Divide each side by '3'.
x = 8

Simplifying
x = 8

See similar equations:

| -x+9y=-10 | | (3+x)2=3x-1 | | 7(y)+4(4)=-28 | | 4x-11=3x-17 | | (5/3x)15/4 | | x+15x+50=180 | | 8x^2+4x=-15 | | X-7.5=9 | | 8x^3+20x^2-12x=0 | | 5/3x15/4 | | {3}{4}z={3}{4} | | 4-3=7 | | (e^3x+5)=12 | | 7(-7)+4x=-28 | | 38/1.62=x/1.00 | | e^3x+5=12 | | 3x+19=58 | | -7x-5=-5 | | 6c*2d= | | 2(2x-1)=x-7 | | 5a*4b= | | -85-10x=98-31x | | 40/1.62=x/1.00 | | 6x+3+6=x-4-2 | | -6.2x-(x-7)=34.6 | | 19x-15=-156 | | 28a+12= | | 92-3x=15+24 | | 2b-7=15 | | 3(x+6)=2x-5 | | 8/4a | | 2x^3-3x^2-32x-15=0 |

Equations solver categories